PURPOSE AT WORK how purpose and innovation drive transformational change. - LINDSTROM, PATTY (ROUTLEDGE, 2026)
This book offers practical frameworks, models, and case studies that will help leaders inspire and lead change effectively, making it an essential resource. It belongs on the desks of founders, entrepreneurs, CEOs, leadership teams, HR professionals, managers, and consultants across industries, as well as business students.Despite the recognition that innovation is key to growth, many companies struggle to implement it effectively. In this groundbreaking work, Patty Lindstrom introduces a three-dimensional framework for growing an organization's capacity to innovate, focusing on defining, communicating, activating, and embedding purpose. Purpose is not just a concept-it's the catalyst for scalable growth and lasting change.Drawing on 30 years of real-world experience and insights from a comprehensive study, Lindstrom explores how purpose impacts individuals, teams, and organizations, driving clarity, confidence, and commitment. She reveals how purpose can enhance innovation capacity, transform organizational culture, and lead to tangible, positive change.
Keywords: Communication in personnel management.; Employees -- Attitudes.; Leadership.; elektronické knihy; electronic books